Value Orientations of the Eastern Family as the Most Important Factor in the Formation of Personality (Eurasian Journal of History, Geography and Economics, 2022)
The article considers the development of the value paths of the eastern family as the most important factor in the formation of the personality. Realizing the priority of family relations in the life of everyone, our state pays special attention to programs for the protection and development of a strong family in the formation of the spiritual and moral image of a person. also to control their implementation.